Ambient temperature and pesticide poisoning: a time-series analysis. Issue 6 (2nd November 2019) - Wang, Junhui; Wang, Honglin; Luan, Guijie; Zhang, Dongfeng
ABSTRACT: Limited studies have explored the association between ambient temperature and the disease burden of pesticide poisoning. Our study aims to estimate associations between daily mean temperature and pesticide poisoning incidence with lag effect. A distributed lag nonlinear model with Poisson distribution was used to examine the nonlinear lagged effects of ambient temperature on pesticide poisoning incidence. Overall, the estimated effects of temperature on pesticide poisoning incidence were non-linear, with higher relative risks (RRs) at hotter temperatures. It was found that the high temperature had acute and short-term effects and then declined rapidly along the lag days with the maximum risk occurring 0 day of exposure. Considering the 5-day cumulative RR for daily mean temperature, the temperature generally showed a positive association with the pesticide poisoning incidence, achieving the maximum risk at 31°C. In general, pesticide poisoning incidence increased with higher temperatures, with the strongest effects occurring shortly.